STRATEGI PENERAPAN DIGITAL MARKETING UNTUK ENTREPRENEUR PEMULA PASCA PANDEMI COVID 19 - Ameilia Damayanti; Mira Munira; Tia Ichwani (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
hit by the co-19 pandemic. Starting from companies to Micro, Small, and Medium Enterprises (MSMEs) are experiencing the impact of this situation. In the midst of this unstable condition, business decisions for both large companies and MSMEs must be made very carefully. MSMEs are experiencing the impact of Covid-19 so they need to make the right decisions and this is based on accurate financial and non-financial data and information. There are various kinds of problems that are generally faced in increasing the success of MSMEs, including aspects of capital, raw materials, weak knowledge in various aspects of management and human resources, as well as weak aspects of recording financial reports. But without sufficient knowledge and understanding of marketing, it will not be easy for MSME actors to be able to promote their quality products. This community service theme is Strategy for Implementing Digital Marketing for Beginner Entrepreneurs After the Covid-19 Pandemic. In this activity, MSME players will be given information and practice on the importance of Digital Marketing Implementation Strategies for Beginner Entrepreneurs after the Covid-19 Pandemic